2012
DOI: 10.1097/aud.0b013e3182280326
|View full text |Cite
|
Sign up to set email alerts
|

Ear Canal Pressure Variations Versus Negative Middle Ear Pressure: Comparison Using Distortion Product Otoacoustic Emission Measurement in Humans

Abstract: Effects of negative MEP and ECP variations on DPOAEs in human ears are comparable, to a great extent, to findings from previous studies on hearing sensitivity in humans and tympanic membrane vibration at the umbo in human temporal bones. The present study demonstrates that positive ECP can be used to simulate negative MEP in research on the middle ear function in live humans. Results also suggest that long-lasting beliefs regarding the ECP effect on the middle ear conduction should be amended: (1) only positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 40 publications
3
11
1
3
Order By: Relevance
“…Composite DPOAE and component magnitudes were reduced during NMEP for almost all the subjects at the majority of the DPOAE frequencies tested. Reductions in DPOAE magnitude during NMEP were apparent between 900 and 3500 Hz and were not solely concentrated in the low frequencies as previously reported (Osterhammel et al 1993;Richter et al 1994;Konradsson et al 1999;Sun & Shaver 2009;Sun 2011).…”
Section: Composite and Component Dpoae Magnitude And Nmepsupporting
confidence: 57%
See 1 more Smart Citation
“…Composite DPOAE and component magnitudes were reduced during NMEP for almost all the subjects at the majority of the DPOAE frequencies tested. Reductions in DPOAE magnitude during NMEP were apparent between 900 and 3500 Hz and were not solely concentrated in the low frequencies as previously reported (Osterhammel et al 1993;Richter et al 1994;Konradsson et al 1999;Sun & Shaver 2009;Sun 2011).…”
Section: Composite and Component Dpoae Magnitude And Nmepsupporting
confidence: 57%
“…When the NMEP was increased to −160 daPa and beyond, the DPOAE magnitude at normal pressure was 10 to 12 dB greater (Sun & Shaver 2009). In addition, NMEP was found to attenuate low-frequency DPOAEs (<1000 Hz) more than high-frequency DPOAEs (Sun & Shaver 2009;Sun 2011).…”
Section: Introductionmentioning
confidence: 95%
“…Za razliku od njih, distorzione otoakustičke emisije su selektivne i omogućavaju lokalizovano ispitivanje kohlee. U humanoj populaciji je moguće porediti uticaj variranja negativnog pritiska u srednjem uvu i u spoljašnjem ušnom kanalu na jačinu odgovora distorzionih otokaustičkih emisija (Sun, 2012). Navedeno istraživanje ukazuje da pozitivan pritisak u spoljašnjem ušnom kanalu može stimulisati negativan pritisak u srednjem uvu, što je važno pri ispitivanju funkcionisanja srednjeg uva.…”
Section: Uvodunclassified
“…Pozitivan pritisak u ušnom kanalu sličan je negativnom pritisku u srednjem uvu ispoljavajući poseban uticaj na odgovore DPOAE (Sun, 2012). Pozitivan ili negativan pritisak u ušnom kanalu (u odnosu na ambijentalni pritisak) redukovao je emisije amplituda za 3 do 6 dB (Naeve et al, 1992), što je u suprotnosti sa našim istraživanjem.…”
Section: Diskusijaunclassified
“…128 Vibration measurements of distortion product otoacoustic emissions have been used for differential diagnosis of cochlear and ME pathologies, 129 and Sun suggested that distorted configuration of the TM and ossicular chain strongly influences the effect of MEP on sound transmission for low frequencies. 130 Dynamic properties of round window membrane provide important data for the study of ME and cochlear mechanics. 131 The 3D structure of the scala tympani terminal, saddle-shaped surface topography, and surface curvature were determined through white light interferometry in an animal model.…”
mentioning
confidence: 99%